Klong yao and the performance of minority identity in the Siamese community of Perlis, Malaysia - Hanafi Hussin (Tanjong Malim, 2019)
Klong yao and the performance of minority identity in the Siamese community of Perlis, Malaysia by Hanafi Hussin